Crystal structure of 1-isopropyl-3-(prop-1-en-2-yl)-1H-pyrazolo[3,4-d]pyrimidin-4-amine, C11H15N5 - Wang Yanjiao; Tang Xiaoqin; Liu Bin (Zeitschrift für Kristallographie - New Crystal Structures)
C11H15N5, monoclinic, P21/c (no. 14), a = 9.5677(16) Å, b = 8.1755(15) Å, c = 14.846(3) Å, β = 93.783(4)°, V = 1158.7(4) Å3, Z = 4, Rgt(F) = 0.0473, wRref(F2) = 0.1425, T = 173 K.